A young Asian woman with thrombosis in the right renal vein and inferior vena cava: A rare case report and literature review. Issue 48 (2nd December 2022) - Hsu, Jhe-Yuan; Li, Tzong-Shiun
Abstract : Introduction: Renal vein thrombosis (RVT) is a rare clinical entity wherein a blood clot forms in one of the major renal veins or its tributaries. Patients with certain risk factors, such as adults with nephrotic syndrome and infants with dehydration, are susceptible to developing it. Patient Concerns: We present a young woman with primary thrombosis in the right renal vein and inferior vena cava. Hormonal therapy and the reception of the Medigen Vaccine Biologics Corporation coronavirus disease 2019 vaccine were the suspected risk factors for developing this disease. Primary Diagnosis, Interventions, Outcomes: The primary thrombosis in the right renal vein and inferior vena cava was diagnosed using abdominal computed tomography (CT), and 90% of the thrombus in the right renal vein was dissolved after ultrasound-assisted catheter-directed thrombolysis followed by urokinase infusion for 1 week. Antibiotics and rivaroxaban were prescribed for 3 days and 5 months, respectively. Cryoprecipitate transfusions based on the level of fibrinogen were also prescribed. No long-term complications were noted in the clinic visits. We demonstrate the results of ultrasound-assisted catheter-directed thrombolysis using urokinase infusion for thrombosis in the right renal vein and inferior vena cava. Lastly, we review the literature discussing RVT relevant to this case. Conclusion: This study reveals the successful use of the novel technique, ultrasound-assisted catheter-directed thrombolysis using urokinase infusion, for the treatment of RVT.